A conurbação Santana do Livramento-Rivera: uma análise morfo-tipológica da micropaisagem fronteiriça - Ilha, Andrea Larruscahim Hamilton (2023)
Located in the Brazil-Uruguay border, Santana do Livramento and Rivera are twin cities, forming a conurbation through the evolution of their road networks. This situation was due to the form of territory occupation, and due to the states’ interests of domination, but above all by a necessity of the peoples who settled in the area. Despite Santana do Livramento and Rivera being perceived as a single urban spot, they share both similarities and differences, due to its distinct colonial origins and being part of two nations, but also by sharing a strong desire of integration. This work looks at the conurbation in search for landscape characteristics, developing a comparative analysis between the cities, identifying what unites and what separates them. The study begins by tracing the urban evolution, then analyzes the elements that compose its morphology, arriving at a reading of the public space use along the borderline and the inter-relationship between these and the social constructions; the appropriations and construction of border spaces imposed by local experiences. It is an examination of the territory identifying the cultural landscape from the characterization of its elements that are inseparable and interdependent as material and immaterial cultural heritage, filled with meanings and symbologies that build local identity. A view that, at times analyzes the territory from a distance, at times from within itself, both important to understand the logic of the border.